Gestión de la comunicación virtual para un aprendizaje significativo con estudiantes de la Escuela de Educación Básica Fausto Molina Molina del cantón Quevedo año 2021 - Zamora Batioja, Iris Johanna (2021)
In the present work we aim to determine the influence of virtual communication on meaningful learning with students from the Fausto Molina Molina Basic Education School. Where the type of habit that schoolchildren do could be manifested, a survey was also carried out on an established population to reach the conclusions where the knowledge of virtual communication management and significant learning are tested. The schoolchildren of said educational entity were analyzed regarding the educational aspect and the implementation of digital platforms in the various investigations that they must comply with. In addition to this, it was learned that some of the educators are not completely involved in what is digital platforms. The methodology used in this research work is the inductive and deductive method, the population of 1397 was taken into account and the sample is 301 participants, after the respective analysis for a descriptive analysis and bibliographic data, it is concluded that the management of communication virtual and meaningful learning as it benefited listeners in their education. Giving significant results Considering attention can benefit collaborative learning, as well as improve interpersonal relationships that favor reducing knowledge in students; Teachers must modernize towards an adaptable teaching style before distance and virtual learning, delineate activities with inclusion, they would improve on the use of computational tools, acquiring skills to manage educational platforms.